2021
DOI: 10.1111/jdv.17430
|View full text |Cite
|
Sign up to set email alerts
|

Patients with primary cutaneous lymphoma are at risk for severe COVID‐19. Data from the Spanish Primary Cutaneous Lymphoma Registry

Abstract: While some papers report an increased risk of COVID‐19 and worse outcomes 1 in oncological patients, others have found no differences 2 . We are not aware of studies assessing risk for COVID‐19 and clinical outcomes of patients with Primary Cutaneous Lymphomas (PCL).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…The apparent resemblance between the genetic features characteristics of the more severe forms of COVID-19 and those implicated in the NHL pathogenesis matches the link between previous viral and microbial infections, including HIV infection, and NHL risk, whether through immunosuppression or other mechanisms [20,21]. In agreement with the hypothesis of shared pathways, a few reports have described an increase in COVID-19 incidence and severity among patients with a diagnosis of primary cutaneous lymphoma (PCL) [22,23] and haematological disease in general [24,25] but not among cancer patients, including lymphoma patients [26]. However, patients with specific NHL subtypes may differ in terms of vulnerability to SARS-CoV-2 infection; it is unclear whether treatment-induced immunosuppression [27,28] and the generic low-rate seroconversion in onco-haematological patients [29] would be exhaustive explanations for such differences.…”
Section: Introductionsupporting
confidence: 55%
“…The apparent resemblance between the genetic features characteristics of the more severe forms of COVID-19 and those implicated in the NHL pathogenesis matches the link between previous viral and microbial infections, including HIV infection, and NHL risk, whether through immunosuppression or other mechanisms [20,21]. In agreement with the hypothesis of shared pathways, a few reports have described an increase in COVID-19 incidence and severity among patients with a diagnosis of primary cutaneous lymphoma (PCL) [22,23] and haematological disease in general [24,25] but not among cancer patients, including lymphoma patients [26]. However, patients with specific NHL subtypes may differ in terms of vulnerability to SARS-CoV-2 infection; it is unclear whether treatment-induced immunosuppression [27,28] and the generic low-rate seroconversion in onco-haematological patients [29] would be exhaustive explanations for such differences.…”
Section: Introductionsupporting
confidence: 55%
“…Consistently with the apparently similar genetic susceptibility features, numerous studies have confirmed a strong link between previous viral and microbial infections, including HIV infection, and NHL risk, whether through immunosuppression or other mechanisms [19,20]. On the other side, a few reports have described an increase in COVID-19 incidence and severity among patients with a diagnosis of primary cutaneous lymphoma (PCL) [21,22] and haematological disease in general [23,24], but not among patients suffering from any cancer, including lymphoma patients [25]. However, NHL subtypes may differ in terms of vulnerability to SARS-CoV-2 infection.…”
Section: Introductionmentioning
confidence: 85%
“…Some studies have evaluated risk factors for severe COVID-19 among patients with MF/SS, which included lymphopenia, chronic organ failure, Sezary syndrome, or active aggressive disease [ 11 ]. Moreover, initial reports indicate that clinical outcomes of patients with MF/SS that were infected with COVID-19 were not significantly different from the general population [ 12 , 13 ]. However, most of these studies were conducted at the beginning of the pandemic and included only the SARS-CoV-2 Alpha variant and non-vaccinated patients.…”
Section: Introductionmentioning
confidence: 99%